SOCIALLY RESPONSIBLE MARKETING AS A TOOL FOR EFFECTIVE INSURANCE COMPANIES’ ACTIVITIES IN WARTIME - Dranus В.; Dranus Л.; Koshkalda І.; Lunkina Т. (Bulletin of Lviv National Environmental University. Series "AIC Economics", 2025)
The article examines the role of socially responsible marketing as a tool for enhancing the efficiency of insurance companies’ operations in the context of war. Amid large-scale military conflict, the Ukrainian insurance market has undergone significant transformations, manifested in decreased client trust, reduced solvent demand, complicated claims settlement, limited coverage of war-related risks, and regulatory uncertainty. The study analyzes recent scientific research and publications addressing the specifics of insurance sector functioning during wartime. The authors highlight that socially responsible practices can ensure not only increased client loyalty and trust but also the financial stability of companies, facilitate the adaptation of insurance products to new conditions, and enhance the transparency and efficiency of processes. The article proposes a set of measures, including the implementation of digital platforms for remote claims settlement, the development of microinsurance and hybrid products with partial public-private coverage, as well as active participation of companies in social and humanitarian initiatives. Special attention is given to the role of state support, including tax incentives, simplification of regulatory requirements, and the creation of special funds to cover war-related risks. The scientific and practical significance of the study lies in the formation of a structured approach to implementing socially responsible marketing, which combines commercial and social goals and creates conditions for enhancing the resilience of the insurance sector under crisis conditions. Further research prospects are associated with developing empirical models for evaluating the effectiveness of SR initiatives, integrating social goals into company strategies, and assessing the efficiency of state mechanisms supporting the insurance market during military conflicts. The proposed approaches contribute to long-term client loyalty, increased competitiveness of companies, and the stability of the insurance sector in Ukraine, even under extremely challenging wartime conditions.